A single-surgeon experience with the internal joint stabilizer of the elbow across 56 cases - John J. Heifner, MD; Gagan Grewal, MD; Christopher J. Castagno, MD; Gil Gontre, MD (JSES International)
Background: Recurrent instability continues to plague outcomes of elbow trauma. Adjuvant stabilization—whether internal or external—is intended to acutely stabilize the elbow and off-load the repair construct(s) during early mobilization. Our objective was to report clinical outcomes for a single-surgeon consecutive series using the internal joint stabilizer (IJS) of the elbow. Furthermore, we intend to describe technical points that have been gleaned from the experience which may provide guidance. Methods: A retrospective follow-up was performed for cases of elbow instability treated with the IJS (Skeletal Dynamics, Miami, Florida, USA) from 2016-2023 with a minimum requirement of 6 months of follow-up. Clinical outcomes and complications including recurrent instability were compiled. Results: Of 87 potential cases, 56 met the inclusion criteria. Simple dislocations (30%) and terrible triad injury (21%) were the most common injury patterns. The mean Mayo Elbow Performance Score was 81 and the mean Disabilities of the Arm, Shoulder, and Hand score was 22.5. Recurrent instability occurred in 5.3% of cases. The mean time to removal was 21.1 weeks. Discussion: Our utilization of the IJS of the elbow has evolved from simple dislocations to complex instability cases. Results demonstrated satisfactory clinical outcomes with low rates of recurrent instability and revision. The ability for early mobilization was a critical determinant for using an IJS in these cases. This advantage carried particular importance in cases that presented subacutely following an extended course of immobilization. Our protocol for removal timing is applied on a case-by-case basis and involves identification of sufficient rehabilitation and clinical stability.